CLINICAL STUDY ON THE ASSESSMENT OF LOCAL STATUS IN PATIENTS WITH PERIODONTAL DISEASE AND DEPRESSION - Bogdan-Constantin Vasiliu; Maria-Alexandra Martu; Irina-Georgeta Sufaru; George-Alexandru Maftei; Ioana Martu; Monica Scutariu; Silvia Martu (Romanian Society of Oral Rehabilitation, 2024)
Chronic periodontitis is a disease caused by several factors; therefore, it can be called a multifactorial disease. Such risk factors include smoking, diabetes, genetics, depression, and stress. Depression is one of the chronic conditions with the highest prevalence worldwide. There is evidence to support the association between psychological disorders and the physiological and behavioral precursors of caries and periodontal disease, suggesting that such a connection may exist. Antidepressant and anxiolytic medication have been associated with decreased salivary flow and poor oral hygiene. The present study aimed to examine the local inflammatory status of patients with periodontal disease and no other systemic conditions and patients with periodontal disease and depression. Between February 2024 and March 2024, we conducted this study on 40 patients aged 20 and 48, evaluating the Quigley Hein Plaque Index, the GI Index of Löe and Silness, and the PBI Index. Analyzing the obtained results, we observed that the values of the periodontal parameters, such as the hygiene index, the gingival inflammation index, and the papillary bleeding index, were significantly higher in the group of patients with periodontal disease and depression compared to the group of patients with only periodontal disease.